2008
DOI: 10.4049/jimmunol.180.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Central Memory but Not Effector Memory CD8+ T Cells Suppress Allograft Rejection

Abstract: Memory T cells respond faster and more vigorously than their naive counterparts and are critical for adaptive immunity. However, it is unknown whether and how memory T cells react in the face of irrelevant Ags. It is generally accepted that bystander memory T cells are neutral in immune responsiveness. In this study, we present the first evidence that bystander central memory (TCM), but not effector memory (TEM), CD8+ T cells suppress allograft rejection as well as T cell proliferation in the draining lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
1
35
1
1
Order By: Relevance
“…In rats, a regulatory CD8 + Foxp3 + CTLA4 + CD45RC lo population has been described; however, controversy exists as to whether these cells suppress via production of cytokines or cell-to-cell contact (42,75). Reports that CD8 + T cells can suppress through TGF-β also exist (48,76). In contrast to these reports, we now describe an IFN-γ-dependent mechanism of CD8 + CCR7 + T cell-mediated immunosuppression in the murine lung.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In rats, a regulatory CD8 + Foxp3 + CTLA4 + CD45RC lo population has been described; however, controversy exists as to whether these cells suppress via production of cytokines or cell-to-cell contact (42,75). Reports that CD8 + T cells can suppress through TGF-β also exist (48,76). In contrast to these reports, we now describe an IFN-γ-dependent mechanism of CD8 + CCR7 + T cell-mediated immunosuppression in the murine lung.…”
Section: Discussioncontrasting
confidence: 44%
“…While the vast majority of studies suggest that memory T lymphocytes potentiate alloimmune responses and inhibit tolerance induction (46,47), it is possible that certain subsets of these cells may suppress alloreactivity (48). It is noteworthy that CD8 + T lymphocytes, including memory CD8 + T cells, were present in the lung at baseline, even in the absence of acute inflammation or alloantigen stimulation ( Figure 6A).…”
Section: Introductionmentioning
confidence: 90%
“…We have previously shown that 'bystander' memory CD8 1 T cells with a central memory T cell (T CM ) phenotype suppress allograft rejection. 37 We also have found that the suppressive capacity of CD8 1 CD122 1 Tregs is partially dependent on IL-10 and that their suppression in vitro is donor-nonspecific. 18 Our findings suggest that the suppression mediated by naturally occurring CD8 1 CD122 1 Tregs is not antigen-specific.…”
Section: Introductionmentioning
confidence: 84%
“…We observed the CD25 − CD8 + expansion in the lung occurred primarily in the CD44 high effector/memory compartment. While it has been shown that naive T cells may undergo bystander proliferation [18,44], the majority of studies report that, after infection, antigen non-specific proliferation occurs in the effector/memory compartment [14,19,[51][52][53]. CD44 high CD8…”
Section: Discussionmentioning
confidence: 99%